MOLTEN-SALT SYNTHESIS OF ANISOTROPIC BAFE12O19 POWDERS - YOON, KH; LEE, DH; JUNG, HJ; YOON, SO (SPRINGER, 1992)
The formation mechanism, morphology, and magnetic properties of anisotropic BaFe12O19 powders prepared by the 0.8 Na2SO4-0.2 K2SO4 molten salt synthesis have been investigated. The reaction can be completed at temperatures lower than 845-degrees-C which is the melting point of the 0.8 Na2SO4-0.2 K2SO4 salt mixture, due to the presence of the low melting phase related to the formation of BaSO4 and Na6CO3(SO4)2. Even at temperatures lower than 845-degrees-C, with the aid of the low melting phase, the morphology of ferrites was thin platelets. Magnetic properties such as coercivity, saturation magnetization, and remanent force are comparable to those found in other processing techniques. The orientation degree of the sintered body was very high due to anisotropic morphology; thus powders from molten salt synthesis are suitable for grain oriented ceramics.
Keywords: BARIUM FERRITE